Asthma diagnosis: a comparison of established diagnostic guidelines in adults with respiratory symptomsResearch in context - Andrew J. Simpson; Sarah Drake; Laura Healy; Ran Wang; Miriam Bennett; Hannah Wardman; Hannah Durrington; Stephen J. Fowler; Clare S. Murray; Angela Simpson (EClinicalMedicine, 2024)
Summary: Background: Considerable variability exists between asthma diagnostic guidelines. We tested the performance characteristics of the European Respiratory Society (ERS), the National Institute for Health and Care Excellence (NICE) and the Global Initiative for Asthma (GINA) guidelines for the diagnosis of asthma in adults. Methods: In this prospective observational study (ISRCTN—11676160, May 2019–June 2022), participants referred from primary care with clinician-suspected asthma underwent comprehensive investigation including: spirometry, bronchodilator reversibility, fractional exhaled nitric oxide, peak expiratory flow variability, bronchial challenge testing with methacholine and mannitol, and responsiveness to inhaled corticosteroid therapy. Results were reviewed by a panel of asthma specialists to determine asthma diagnosis (reference standard) and compared to each diagnostic test and the ERS, NICE and GINA diagnostic algorithms (index tests). The sensitivity, specificity, positive predictive and negative predictive values were calculated. Findings: One hundred and forty adults were enrolled and 118 given a definitive diagnostic outcome [75 female; mean (SD) age 36 (12) years; 70 (59%) with asthma] and included in the analysis. Sensitivity of individual tests was poor (15–62%), but they provided good specificity at the most stringent thresholds (range: 88–100%). The sensitivity/specificity of ERS, NICE and GINA was 81/85%, 41/100% and 47/100%, respectively. Concordance between guidelines was only moderate (Cohen’s Kappa 0.45–0.51). Interpretation: Current guidelines for the diagnosis of asthma in adults provide either excellent specificity but low sensitivity (GINA and NICE) or only reasonable sensitivity and specificity (ERS). All guidelines therefore have limitations with regards to their clinical application; new guidelines are needed but should be tested prospectively before roll out. Funding: This work was supported by the Manchester NIHR Biomedical Research Centre (BRC) (grant no. BRC-1215-20007, and NIHR203308), Asthma UK/Innovate (grant no. AUK-PG-2018-406), GSK ID 212474 and North West Lung Centre Charity.